Proton Sound Detector for beam range/dose measurement in FLASH hadron therapy. (1st July 2022) - Vallicelli, E.A.; Baschirotto, A.; De Matteis, M.
Abstract: Proton Sound Detectors (ProSDs) sense (at low latency, <1 ms) the thermoacoustic signal generated by the fast energy deposition at the Bragg peak of a proton beam penetrating an energy absorber. ProSDs are especially promising for experimental monitoring of high pulse rate (FLASH) hadron therapy treatments working in-sync with the beam. This paper presents a mixed signal detector, capable of sensing and processing high rate (1k beam shots/sec) ionacoustic signals with low latency (<1 ms). The system was validated by measuring the dose deposition of a 20 MeV proton beam in water, achieving 3.43% precision (±2.75 GyRMS ) after 50 ms acquisition (77.56 Gy total dose deposition).